AN ASSESSMENT ON THE EFFECT OF STREET CHILDREN ON SECURITY OF MBALE INDUSTRIAL CITY DIVISION. - MATANDA ISAAC (My University, 2024)
ABSTRACT This study investigates the factors contributing to the increasing number of street children in Mbale Industrial City Division, assesses the nature and extent of their involvement in criminal activities, and explores strategies to curb their impact on local security. The research employs a mixed-methods approach, combining quantitative and qualitative data gathered from 197 respondents, including street children, community leaders, law enforcement officers, and social service providers. Descriptive and inferential analyses using SPSS were conducted to identify significant trends and correlations. The findings reveal that poverty, family breakdown, and lack of access to education are primary drivers of children turning to the streets. Additionally, street children in Mbale Industrial City Division are significantly involved in petty crimes such as theft and drug-related activities, which negatively affect community security. The study recommends a multi-faceted approach to address the issue, including enhanced social protection programs, family support services, community policing, and the establishment of rehabilitation centers. The research underscores the need for coordinated efforts between government agencies, non-governmental organizations, and community stakeholders to effectively reintegrate street children into society and mitigate the associated security risks. These recommendations, if implemented, could significantly reduce the number of street children and improve the security and well-being of the community.